A semiotic analysis of political cartoons on the first 100 days of Anies Baswedan government - Nindya Hasanah; Didin Nuruddin Hidayat (Universitas Islam Sultan Agung, 2020)
Nowadays, information can be conveyed not only through words, but also through images. An image is also a form of one-way communication because, through an image, people can convey the meaning. This study aimed to describe Anies Baswedan’s political cartoons on his first 100 days as a governor. This study employed a qualitative research approach, and the content or document analysis as the research design. The researchers collected and analyzed the data dealing with the relationship between the utterances and Anies’ cartoons on his first 100 days as Jakarta’s governor. In analyzing the data, some steps were taken: first, categorizing the sign into icon, symbol, index using a typology of signs; second, interpreting the meaning of the political cartoons; last, drawing conclusions based on the result of the analysis. The study found that the signs in those political cartoons had powerful meanings to convey the aspiration of Indonesian people freely towards Anies’ government. Also, the fact that the cartoons were in the forms of images eased the readers in understanding the meanings behind them, and the political cartoons deal with the relationship between visual and verbal signs of cartoons because it will be helpful for the researchers to know about events depicted in those cartoons.The study also offers some potential use of cartoons for language teaching, even though the challenges of employing them are evident.